Studying the Absorption Refrigeration System powered by Thermal Waste and Electricity Conversion from Photovoltaic - Priyo Adi Sesotyo; Sunaryo Sunaryo; Zainal Arifin; Puji Basuki (Nacreva Publisher, 2022)
Currently, buildings are responsible for 32% of the world’s energy consumption, with the most massive energy-consuming device in facilities being the refrigeration system. Photovoltaic is an alternative source of energy without causing environmental damage. Solar Refrigeration is an attractive solution because when there is much solar radiation, peak thermal energy is generated, and a lot of cooling capacity is needed. In this research, the amount of PV modules used as the LiBr-H2O Absorption Refrigeration System’s primary energy source is investigated. PV modules have a dual function, namely as a producer of electric power and producing thermal waste, both of which can be used as energy sources to drive this refrigeration system. In this thermal waste, two thermal sources, namely thermal convection and thermal radiation, accumulate to activate heat exchange at the LiBr-H2O absorption refrigeration system’s generator side. For electrical power from the PV module, it is used to run the air heater to increase the temperature until it reaches the optimum point for hot water supply between 65 to 70 oC. The results are that at least 100 modules of 100Wp Monocrystalline PV Module are needed to drive the LiBr-H2O absorption refrigeration system. Still, it is limited to 15.00, after which the energy source is switched back to electricity from PLN because, after 15.00, many PV modules are required and takes up a large enough space.